Consumer Preferences in Germany for Bio-Based Apparel With Low and Moderate Prices, and the Influence of Specific Factors in Distinguishing Between These Groups - Stahl, Florian Felix; Emberger-Klein, Agnes; Menrad, Klaus (Frontiers in Sustainability, 2021)
Bioplastics are a potential alternative to conventional plastics when it comes to reducing the use of the fossil resource of crude oil. There have been so far very few studies on the consumption of bio-based apparel and consumer preferences relating to it. Within this study, an online survey was conducted with 1,673 participants that is representative of the German population over the age of 16, including a choice-based consumer experiment with a bio-based rain jacket. Using latent class analysis, two clusters of consumers (39% of respondents) were identified with acceptance of moderate prices for such bio-based products. The other 61% of consumers showed preferences for the lowest prices of the tested bio-based rain jacket. A discriminant analysis revealed that the intention to purchase bio-based apparel, the Green Consumer Value and subjective norms of bio-based apparel were the strongest significant factors when distinguishing between consumer groups of bio-based apparel with a ‘preference for a low price’ and those showing ’acceptance of a moderate price’. This study helps to better illuminate the heterogeneity of consumer preferences for bio-based apparel related to pricing strategies and supports building up of a supply chain for such products.